BMD impact on silicon fin defect at TSV bottom. Issue 13 (1st June 2014) - Zhang, Dingyou; Thangaraju, Sarasvathi; Smith, Daniel; Kamineni, Himani; Klewer, Christian; Scholefield, Mark; Lei, Ming; Vikram, Abhishek; Lim, Victor; Kim, Wonwoo; Alapati, Ramakanth
Abstract : A new type of through‐silicon via (TSV) defect, silicon fin defect, which was found after the TSV deep‐reactive‐ion‐etching process at the TSV bottom is reported. These defects are considered killer TSV defects that may cause process or mechanical failures and have to be eliminated. A scanning electron microscope automatic process inspection approach, which is non‐destructive and proven to be effective, has been established to image the fin defects at the bottom of the trench. A possible root cause of this defect is also explored. Both simulation and benchmarking test results indicate that bulk micro defects (BMDs) in the silicon substrate could serve as a micro‐mask during etching and result in silicon fin defects.